Musculoskeletal simulation of sports motion considering tension distribution in a whole body compression garment - Nakashima, M.; Hosoya, T.; Shimana, T. (Procedia Engineering, 2016)
Compression garments are widely used in various sports activities. Since the cloths in a compression garment are sufficiently attached to the human body, it is possible for a compression garment to have particular mechanical functions by appropriately arranging the tension distribution in the garment. However, the effects of such garment on muscle activity have not been sufficiently investigated yet. Therefore, a method of musculoskeletal simulation for such problems were developed in the present study. In the developed musculoskeletal model, particular belt-like parts of cloths which had larger tension against stretch were modelled as virtual ligaments. In order to distribute the virtual ligaments, 403 reference points for upper half of the body were defined on the whole body in the musculoskeletal model. These points could be used as start, end and via points for the virtual ligaments. As an example of analysis, a running motion was analyzed in the present study. The running motion was acquired from the experiment using motion capture system, and put into the simulation model. One simple pattern of tension distribution was examined by the simulation. From the simulation, it was confirmed that the muscle activity changed according to the tension of the belt-like cloths. Therefore the developed simulation method will be useful for the design (the arrangement of the belt-like cloths) of the whole body compression garments.